Thinking the School from Chaos to Cosmos: A Philosophical and Pedagogical Reflection on the Crisis - Mosquera Mosquera, Carlos Enrique (2026)
This article examines the crisis of schooling in postmodernity, arguing that the decline of modern grand narratives and the transition toward a liquid society have left educational institutions without a clear pedagogical horizon. It critiques the increasing influence of consumerism and the emphasis on flexibility in education, trends that weaken the transmission of cultural values and undermine academic rigor. As an alternative, the article proposes the figure of the “rebel teacher,” who reintroduces so-called “useless knowledge”—such as art, poetry, painting, and the humanities—as a way to resist the dominant utilitarian logic. This pedagogical stance seeks to create a space for reflection and resistance to the postmodern void through the establishment of a singular pedagogical time (kairos) within the curriculum, thereby enabling a more holistic and humanistic educational experience.Finally, the article underscores the importance of recovering a sense of purpose and order in education, even if only in a provisional manner.